SILENT CRISIS IN CHILDREN: PERAN KOMUNIKASI KELUARGA DAN POLA ASUH ORANG TUA TERHADAP PEMBENTUKAN KEPERCAYAAN DIRI ANAK USIA SEKOLAH - Sri Rahayu; Dian Apri Nelyanti; Amirul Kadafi; Miftachul Sobirin (Akademi Kebidanan Harapan Bunda Bima, 2026)
Self-confidence is a crucial aspect of psychosocial development in school-aged children. Low self-confidence can negatively affect academic achievement, social interactions, and overall mental well-being. The family environment, particularly family communication and parenting styles, plays a significant role in shaping children's self-perception and confidence. However, modern social changes and increasing demands of daily life have reduced the quality of family communication, creating a